Subchronic Inhalation of TiO2 Nanoparticles Leads to Deposition in the Lung and Alterations in Erythrocyte Morphology in Mice - Kulich, Pavel; Marvanová, Soňa; Skoupý, Radim; Škorič, Miša; Vysloužil, Jan; Šerý, Omar; Mikuška, Pavel; Alexa, Lukáš; Coufalík, Pavel; Křůmal, Kamil; Moravec, Pavel; Večeřa, Zbyněk; et al. (Journal of applied toxicology, 2025)
TiO2 nanoparticles (NPs) are extensively used in various applications, highlighting the importance of ongoing research into their effects. This work belongs among rare whole-body inhalation studies investigating the effects of TiO2 NPs on mice. Unlike previous studies, the concentration of TiO2 NPs in the inhalation chamber (130.8 μg/m3) was significantly lower. This 11-week study on mice confirmed in vivo the presence of TiO2 NPs in lung macrophages and type II pneumocytes including their intracellular localization by using the electron microscopy and the state-of-the-art methods detecting NPs' chemical identity/crystal structure, such as the energy-dispersed X-ray spectroscopy (EDX), cathodoluminescence (CL), and detailed diffraction pattern analysis using powder nanobeam diffraction (PNBD). For the first time in inhalation study in vivo, the alterations in erythrocyte morphology with evidence of echinocytes and stomatocytes, accompanied by iron accumulation in spleen, liver, and kidney, are reported following NP's exposure. Together with the histopathological evidence of hyperaemia in the spleen and kidney, and haemosiderin presence in the spleen, the finding of NPs containing iron might suggest the increased decomposition of damaged erythrocytes. The detection of TiO2 NPs on erythrocytes through CL analysis confirmed their potential systemic availability. On the contrary, TiO2 NPs were not confirmed in other organs (spleen, liver, and kidney); Ti was detected only in the kidney near the detection limit.
Keywords: titanium dioxide nanoparticles; electron microscopy; inhalační expozice; lung; Nanoparticles; Administration, Inhalation; Inhalation Exposure; Erythrocytes; Toxicity Tests, Subchronic; tkáňová distribuce; Lung; powder nanobeam diffraction; zvířata; kovové nanočástice; myši; plíce; titan; Mice; cathodoluminescence; Metal Nanoparticles; Titanium; Tissue Distribution; Male; nanočástice; erytrocyty; aplikace inhalační; Animals; mužské pohlaví; testy subchronické toxicity